Study of Hematological Changes in Local Goats (Capran Aegagrus) at Al-Najaf Province, Iraq - Mujeeb Towfik Shamsa (Institute of Medico-legal Publications Pvt Ltd, 2020)
Goat is among widespread small ruminants in the Iraq and important animal provides nutrient resourcesfor as well as economical source. The blood values and hematologicalparameters can be greatly affected byenvironmental factors such as stress, low grassland pasture, parturition and climate. Thus, it can be reflectedby blood analysis and reliable medium for health and illness status of individual animals.200 of normal and healthy goats (90 males and 110 Females) were selected depending on clinical examinationin Al-Najaf slaughterhouse (Al-Najaf, Iraq). The study was conducted during the summer season. The goutswere divided into subgroups according to sex and age. Then, Blood samples were collected from the jugularvein for the determination of hemoglobin, packed cell volume, red blood cells count, and white blood cellscount and sub determination of white blood cell was included neutrophils, small and large lymphocytes,monocyte, eosinophil, basophil and band-cell. Result showed there are nonsignificant different betweenmale and female hematological parameters in all age period except small lymphocytes in gout larger than1 year old and Neutrophils for less than 6-month age. In Conclusion: This study includes values that areconsidered to be the first to be published for the difference in local goats’ breeds (Capran Aegagrus) At Al-Najaf Province, Iraq. Such data is considered as preliminary data which can be used as a reference for furtherstudies.Aim of Study: The aim of the study was to measure hematological parameters in order to monitor the healthstatus of goat breeding with different age in males and female goat.